( L^p ,L^q ) Properties of the Potential-Type Integrals Associated to Non-doubling Measures - Hajibayov, Mubariz G. (Sarajevo Journal of Mathematics, 2024)
The ( L^p ,L^q ) boundedness of the potential-type integrals associated to non-doubling measures are investigated. 1991 Mathematics Subject Classification. 31B15, 46E35